Metaphor in Arab Political and Diplomatic terms and it’s translation into Spanish - Abdulsahib, Hiyam Kadhim; Mohesan, Mohamed Hashim (Al-Adab Journal, 2022)
Metaphor is one of the tools that describe something by resemblance. It’s used to give more focus to an idea or a feeling. It can be said that metaphor contributes to the building of any kind of discourse, used in the political and diplomatic fields; we find it in political or diplomatic texts, especially in media channels. This work explains some information about political and diplomatic metaphors with examples taken from press. The goal from choosing political metaphors is to explain their role in the structure of the political and diplomatic term. We have chosen seven political metaphors and six diplomatic terminologies from BBC Arabic (an Arabic news channel). For example: the term Arab Spring, a storm in a teacup.